The Time-Dependent Behavior of Glulam Beams from European Hornbeam - Jelena Lovrić Vranković; Ivica Boko; Ivana Uzelac Glavinić; Neno Torić; Mario Abramović (Buildings, 2023)
This paper presents the results of an experimental investigation of glued laminated timber (glulam) beams made from European hornbeam (Carpinus betulus L.) under constant loading for three months. Glulam beams were experimentally tested as a part of the last phase of the research project conducted by Drvene konstrukcije Ltd. and the Faculty of Civil Engineering, Architecture and Geodesy, Split. Beams were loaded in four-point bending tests with the applied load levels of 20% and 30% of the maximum force obtained from previously performed short-term tests. The experiments were carried out under minor environmental changes at the specialized laboratory unit at the Faculty of Civil Engineering, Architecture, and Geodesy, Split. The objective of this study is to present the research results of bending creep tests for hardwood species not included in the European Assessment Document. The experimentally obtained deflection-time curves were fitted with the power law equation used for the prediction of creep behavior. The results indicate that the power law fits well with experimental data. A comparison with requirements from Eurocode 5 is given.